Aplikasi Pengukuran Kayu Berbasis Android pada SMK Kehutanan (Studi Kasus SMK Kehutanan Sobat Bumi) - Erna Liani; Riki Purba; Novita Anggraini (LPPM STT Terpadu Nurul Fikri, 2024)
Android applications have become a popular operating system throughout the world because of their development, Android applications also have an influence on the world of education as supporting learning media. Sobat Bumi Forestry Vocational School requires media and tools to practice measuring wood. Processing and media that are still manual result in frequent human errors or the media used is often damaged and also wastes time. In this problem, media and tools or an Android-based wood measurement application are needed to help and simplify calculations, processing and recording of data so that the resulting data is more accurate. This research uses data collection methods and the waterfall method as application system development. At the code writing stage, the standard formula for measuring Indonesia wood is used, namely 0,7854 x d x p /10.000. The research results show that the Android-based wood measurement application helps Forestry Vocational School students in the process of calculating wood volume more accurately. The media or tools for recording and processing data will be more practical and can be used as a medium for implementing Android applications.